2012
DOI: 10.1111/j.1432-2277.2012.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic polymorphisms on tacrolimus pharmacokinetics and the clinical outcome of renal transplantation

Abstract: Summary We retrospectively examined the association of polymorphisms in the CYP3A, CYP2J2, CYP2C8, and ABCB1 genes with pharmacokinetic (PKs) and pharmacodynamic (PDs) parameters of tacrolimus in 103 renal transplant recipients for a period of 1 year. CYP3A5 expressers had lower predose concentrations (C0)/dose and higher dose requirements than nonexpressers throughout the study. Among CYP3A5*1 carriers, those also carrying the CYP3A4*1B allele showed the lowest C0/dose, as compared with CYP3A4*1/CYP3A5*3 carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 47 publications
(63 reference statements)
2
59
2
2
Order By: Relevance
“…4,5) However, a newly identified SNP in the CYP3A4 gene, CYP3A4*1G affects the pharmacokinetics of some drugs. 7,9,21,22) Although some SNPs in the CYP3A4 gene such as CYP3A4*1B and CYP3A4*22 have been reported to affect the pharmacokinetics of tacrolimus, 17,23) the frequencies of CYP3A4*1B and CYP3A4*22 have not been observed in Chinese and Japanese patients. 19,[24][25][26] In the present study, CYP3A4*1G genotype showed a significant association with the C/D ratio of tacrolimus in living-donor liver transplant patients comparable with data reported in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5) However, a newly identified SNP in the CYP3A4 gene, CYP3A4*1G affects the pharmacokinetics of some drugs. 7,9,21,22) Although some SNPs in the CYP3A4 gene such as CYP3A4*1B and CYP3A4*22 have been reported to affect the pharmacokinetics of tacrolimus, 17,23) the frequencies of CYP3A4*1B and CYP3A4*22 have not been observed in Chinese and Japanese patients. 19,[24][25][26] In the present study, CYP3A4*1G genotype showed a significant association with the C/D ratio of tacrolimus in living-donor liver transplant patients comparable with data reported in kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…3,6) The CYP3A5*3 genotype is well-known to be associated with the pharmacokinetics of tacrolimus in patients with liver, kidney and heart transplant. [17][18][19][20] Hepatic and intestinal CYP3A5 plays a significant role in the clearance of tacrolimus after oral administration in liver transplant patients. 4,5) However, a newly identified SNP in the CYP3A4 gene, CYP3A4*1G affects the pharmacokinetics of some drugs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CYP450 1A2 gene polymorphisms are thought to be involved in the metabolism of theophylline; a study by Uslu et al (2010) suggested that genetic alterations in CYP1A2 play a role both in the pharmacogenetics of theophylline and in the development of chronic obstructive pulmonary disorder. Gervasini et al (2012) found that the CYP3A4*1B-CYP3A5*1 haplotype may have a profound impact on tacrolimus pharmacokinetics, which may be related to the occurrence of toxicity or acute rejection in renal transplant recipients treated with tacrolimus.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent variants are TPMT*2, TPMT*3A and TPMT*3C [Cheok et al, 2009;Gervasini et al, 2012].…”
Section: B21 Polymorphisms That Influence Drug Pharmacokineticsmentioning
confidence: 99%